2021
DOI: 10.1177/02666669211005819
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Facebook use among students and its impact on collaborative learning

Abstract: The purpose of this study is to investigate the determinants of Facebook use among university students in Jordanian universities, and its impact on collaborative learning. The study compares Facebook use between students of social sciences disciplines and students of sciences disciplines. The study used a quantitative research approach. The research instrument used is a questionnaire. The results of the study showed that the relationship between Facebook use and collaborative learning is above average, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 78 publications
2
8
0
Order By: Relevance
“…Further still, the findings in this study uphold the findings by Alwreikat et al (2021) who in a study to investigate the determinants of Facebook use among students and its impact on collaborative learning held the opinion that the more time spent on Facebook the better learner academic achievement students achieve through collaborative learning. Alwreikat et al (2021) Muthui and Sirera (2017) who in a survey study to establish the implications of time spent on social media on academic performance by adolescents in public day secondary schools in Nakuru East constituency penned that most adolescents spend most time on social media such as FSNP for social interactions which had the potential of contributing to their low academic achievement. Muthui and Sirera further argued that students resisted school rules and regulations to sneak mobile devices to use for social interactions instead of academic use.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Further still, the findings in this study uphold the findings by Alwreikat et al (2021) who in a study to investigate the determinants of Facebook use among students and its impact on collaborative learning held the opinion that the more time spent on Facebook the better learner academic achievement students achieve through collaborative learning. Alwreikat et al (2021) Muthui and Sirera (2017) who in a survey study to establish the implications of time spent on social media on academic performance by adolescents in public day secondary schools in Nakuru East constituency penned that most adolescents spend most time on social media such as FSNP for social interactions which had the potential of contributing to their low academic achievement. Muthui and Sirera further argued that students resisted school rules and regulations to sneak mobile devices to use for social interactions instead of academic use.…”
Section: Discussionsupporting
confidence: 84%
“…Oyelere et al (2021) observed that right self-regulated learning strategies in online courses motivate students to strive for a good teamwork experience, leading to increased interest in online learning and increased academic achievement. Similarly, while Alwreikat, Zaid, and Shehata (2021) in a study to investigate the determinants of Facebook use among students and its impact on collaborative learning hold the opinion that the more time spend on FSNP the better learner academic achievement students achieve, the learning activities should be closely monitored by the tutors. Alwreikat et al (2021) emphasized on the need for teachers to regulate the time to control learner concentration on the content learnt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social science disciplines had a stronger positive association between perceived benefits and Facebook use. This data confirms that students utilize Facebook for collaborative learning and academic communication (Alwreikat et al, 2022).…”
Section: Facebooksupporting
confidence: 77%
“…As a result of the emergence of information technologies in the past few years, the landscape of scholarly communication practices has been under exploration (Manca and Ranieri, 2017; Ward et al , 2019; Hook, 2019; Alwreikat et al , 2021; Watkinson et al , 2016; Kramer and Bosman, 2016). The scholars have found that the elements of the scholarly communication system have been dramatically affected.…”
Section: Change In Scholarly Communication Landscapementioning
confidence: 99%